2017
DOI: 10.18265/1517-03062015v1n37p64-70
|View full text |Cite
|
Sign up to set email alerts
|

Estudo experimental do limão Tahiti (Citrus latifólia Tanaka): composição físico-química e de minerais da polpa in natura e do resíduo albedo

Abstract: <p>The present work aimed to evaluate the physical-chemical and mineral parameters of the in natura pulp and the albedo residue of the Tahiti lemon. The pulp was extracted on a stainless steel horizontal removing device and refined in a sieve with a mesh size less than 1.0 mm. The albedo residue was separated and manually dried in a kiln with forced air circulation at a temperature of 55 ± 2°C until constant mass. The physico-chemical analyzes for the pulp in natura were: total solids (TS), soluble solid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…On the other hand, the mean Brix values did not significantly change during storage (Table 5). Marroquim et al (2019) have reported a TSS level between 2.00° and 4.10° Brix in fruit-pulp beverages and between 1.85 and 5.50° Brix in fresh-fruit beverages, indicating that fresh fruits contain 5.5° Brix from kale leaves (Mucke;Massarolo;Mucke, 2012), 8.16° Brix for Tahiti lime (Brito et al, 2017), and 11.62-13.30°…”
Section: Physicochemical Analysismentioning
confidence: 99%
“…On the other hand, the mean Brix values did not significantly change during storage (Table 5). Marroquim et al (2019) have reported a TSS level between 2.00° and 4.10° Brix in fruit-pulp beverages and between 1.85 and 5.50° Brix in fresh-fruit beverages, indicating that fresh fruits contain 5.5° Brix from kale leaves (Mucke;Massarolo;Mucke, 2012), 8.16° Brix for Tahiti lime (Brito et al, 2017), and 11.62-13.30°…”
Section: Physicochemical Analysismentioning
confidence: 99%
“…Tahiti limes used to perform the procedures were purchased at the local market and the production of the albedo flour was based in experiments performed by Brito et al [12]. First, the limes were washed in running water with neutral detergent to remove dirt from the surface, for at least 10 min, and immediately rinsed, sanitized by immersion for 10 min in chlorinated water (2.5% active chlorine) [15], manually peeled and separated in fractions (flavedo, albedo and bagasse).…”
Section: Obtention Of Albedo Flour Of Tahiti Limementioning
confidence: 99%
“…Most of the lime production is driven to domestic and foreign markets for fresh consumption. Due to cultural issues, the consumption of this fruit in the Brazil is restricted as an ingredient, and its constituents are not fully used [12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation